Eksistensi Mahasiswa PPL Dan Praktikum Dalam Meningkatkan Motivasi Belajar Peserta Didik Di SMP Negeri 5 Panyabungan - Novebri Novebri; Nur Jannah; Ruly Regar; Elwina Sari (Universitas Maritim AMNI Semarang, 2024)
This research aims to get answers to discussions regarding the existence of STAIN Madina PPL students, regarding students' learning motivation and the role of PPL students in increasing learning motivation. This research is qualitative field research. The research subjects were students at SMP Negeri 5 Panyabungan using observation, interview and documentation instruments. Most of them feel unprepared and lack confidence when carrying out teaching practices. However, they do not face difficulties in mastering the teaching material. PPL STAIN Madina students have a positive influence on students' learning motivation. seen from the responses of students who were happy with the presence of PPL students. Efforts to play an optimal role in increasing students' learning motivation are carried out by creating good communication with students, implementing appropriate learning strategies and establishing good cooperation with tutors and supervisors.